Ultra low RIN, low threshold AlGaInAs/InP BH-DFB laser - Ren Jianhua; Xing Yanhui; Han Jun; Sun Tianyu; Xing Zheng; Yin Can; Zhang Baoshun (Journal of the European Optical Society-Rapid Publications, 2024)
This study presents a comparative analysis of AlGalnAs buried heterostructure laser diodes by using dual-channel ridge-waveguides. Different shaped channels, including bowl shaped groove and vertical groove, are explored. Using a vertical groove structure, we achieved an output power of 90 mW at 25 °C with a threshold current of only 4 mA. This represents a 3.6-fold increase in output power compared to the BH-DFB structure. At a high temperature of 85 °C, the laser maintains a side-mode suppression ratio of over 45 dB at the maximum power point. The laser’s relative intensity noise in the 0–40 GHz frequency range is less than −162.8 dB/Hz when operated at 300 mA with the chip butterfly packaged. These findings underscore the robustness, reliability, and high-performance capabilities of the developed DFB laser, highlighting its potential for various practical applications.